2016
DOI: 10.1039/c6ra21871g
|View full text |Cite
|
Sign up to set email alerts
|

Sugar based amphiphiles: easily accessible and efficient crude oil spill thickening agents

Abstract: In this work, we demonstrate the use of biomass for the catalytic production of phase-selective gelators (PSGs) as a cost-effective, environmentally benign and ideal method for crude oil spill remediation, as well as execute the study exclusively in crude oil. The use of PSGs has recently provided great promise relative to that of their traditional counterparts. However, the use of PSGs with crude oil is much more complicated due to its complex composition. All of the current PSG methods are demonstrated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…John and co-workers have extended their study with mannitol and sorbitol-based gelators by synthesizing the long fatty acid derivatives 97-101 by adopting enzyme assisted synthesis (Figure 16). [59] Out of several acyl derivatives, compounds 97-101 exhibited good gelation properties towards variety of crude oils. Being superior gelator among them, compound 97 was used for model OSR studies.…”
Section: Application Of Psogs As Solution In Water-immiscible Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…John and co-workers have extended their study with mannitol and sorbitol-based gelators by synthesizing the long fatty acid derivatives 97-101 by adopting enzyme assisted synthesis (Figure 16). [59] Out of several acyl derivatives, compounds 97-101 exhibited good gelation properties towards variety of crude oils. Being superior gelator among them, compound 97 was used for model OSR studies.…”
Section: Application Of Psogs As Solution In Water-immiscible Carriermentioning
confidence: 99%
“…Toluene was used as the carrier solvent for the application of these gelators. John and co‐workers have extended their study with mannitol and sorbitol‐based gelators by synthesizing the long fatty acid derivatives 97 – 101 by adopting enzyme assisted synthesis (Figure ) . Out of several acyl derivatives, compounds 97 – 101 exhibited good gelation properties towards variety of crude oils.…”
Section: Application Of Psogs As Solution In Water‐immiscible Carriermentioning
confidence: 99%
“…However, the major oil-spills caused by crude-oil, mainly during transportation through sea or during drilling which is associated with more rigorous challenge for recovery, are mitigated by sugar based gelators; are reported by very few authors. 33,39,43,44 As already discussed earlier that heating-cooling process is tedious and not viable over sea. Room temperature gelation is preferred choice for these type of typical applications.…”
mentioning
confidence: 96%
“…12, Sugar based gelators are one of the important class from economic perspective, ease of synthesis and biocompatibility. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] John and co-workers in 2010 demonstrated a model study with reduced sugar (mannitol) based amphiphile PSGs for oil spill treatment. 29 Following the pathway of selective protection of hydrophilic -OH groups in sugars by hydrophobic groups, several authors have reported mannitol, [29][30][31][32][33] sorbitol, [34][35][36][37] glucose, [38][39][40] galactose, 41,42 arabinose 43,44 and other sugar based PSGs.…”
mentioning
confidence: 99%
See 1 more Smart Citation